Preoperative CT and Intra-Operative Physical Space Registration of the Spine Using an Articulated Model: a Phantom Study - Marzieh Ershad; Alireza Ahmadian; Hooshang Saberi (Frontiers in Biomedical Technologies, 2014)
Purpose: Due to the difference in spine curvature in intra-operative and preoperative situations in image guided spine surgery (IGSS), each vertebra needs to be registered separately. This can be done by collecting anatomical landmarks on the patient’s anatomy using a pointer and a tracker, and registering them with corresponding points on the 3D model of CT images. Registering each vertebra using this method can be a tedious and time consuming task. Registering the spine using an articulated model, which incorporates the inter-vertebral transformation between consecutive vertebra, introduces a simple and efficient framework. Methods: In this paper, a deformation (extension) is applied to the lumbar vertebra of a spine phantom. Local coordinate systems are defined separately for each vertebra in the 3D model reconstructed from CT images before deformation and on the phantom after deformation. The intervertebral transformations for consecutive vertebrae are calculated in the 3D models. Registration is carried out using the local coordinate systems and the intervertebral transformations. Results: This method was evaluated using point based registration with known corresponding points in both spaces. These results were also compared to those of surface based registration. As indicated by the results, an average improvement of 30% in the registration accuracy was achieved compared to the surface based registration method with acquired random points. Conclusion: The proposed method decreases the registration time by eliminating the need to acquire surface points on each individual vertebra. It is also applicable in situations with defected vertebrae where anatomical landmarks are difficult to distinguish.